Influence of the Accounts Receivable Factoring on the Firm Value - Michalski, Grzegorz (Faktoring i jego wpływ na wzrost wartości przedsiębiorstwa faktoranta, 2009)
Steering the operating cycle is counting and he influences the value of the company. Applying the factoring which can also influence is one of methods of shortening this cycle for curbing the operating risk but because of that for lowering rates of the cost of capital financing the enterprise. The basic financial purpose of an enterprise is maximization of its value. Operating cycle management should also contribute to realization of this fundamental aim. The enterprise value creation strategy is executed with a focus on risk and uncertainty. This paper presented the consequences for the firm that can result from changes in operating cycle and operating risk that are related to using factoring as instrument to short target operating cycle of the firm and advantages resulting in risk reduction caused by transferring it to factor. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 48, s. 566-574